2013
DOI: 10.1007/978-3-642-39031-9_26
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Drawbacks of Reference Architectures

Abstract: Abstract. Reference architectures (RA) have been studied to create a consistent notion of what constitutes them as well as their benefits and drawbacks. However, few empirical studies have been conducted to provide evidence that support the claims made. To increase this evidence, this paper investigates the actual industrial practice of using RAs. The study consists of a survey with 28 stakeholders from everis, a multinational consulting company based in Spain. We report the findings and contextualize them wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 8 publications
0
18
0
2
Order By: Relevance
“…This drawback was not reported in previous studies of software reference architectures [3,17]. It becomes necessary to balance between stability and updates of AUTOSAR, since some practitioners find that there are too many releases.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…This drawback was not reported in previous studies of software reference architectures [3,17]. It becomes necessary to balance between stability and updates of AUTOSAR, since some practitioners find that there are too many releases.…”
Section: Discussionmentioning
confidence: 88%
“…Finally, we plan to represent and aggregate the empirical evidence of this survey with the benefits and drawbacks reported in other studies about software reference architectures [3,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported the effects (i.e., benefits and drawbacks) caused by the use of SRAs, as well as the percentage in which they appeared in practice [3]- [5]. Other works have focused on analyzing the practices and constraints of SRA, and qualitatively reported how they moderate or imply the aforementioned effects [1], [2].…”
Section: Contribution Of This Aggregation To the Theory On Srasmentioning
confidence: 99%